Profiles - Rina Saeed Khan (Lahore, Pakistan Vanguard Books Ltd., 1998)
Biographical sketches of prominent Pakistani personalities; collection of articles previously published in the weekly Friday Times from 1992-1998.
Include Illustration
Keywords: Pakistan